Additive Effects of Macromolecular Crowding and Confinement on Protein Stability - Bui, Phuong Thuy; Hoang, Trinh Xuan (Communications in Physics, 2018)
Folding of protein in vivo typically occurs in a solution highly crowded by macromolecules and in a confined space. It has been found that the effects of macromolecular crowding and confinement are similar in terms of the enhancement of protein stability. However, these effects are often considered separately in theoretical and simulation studies. In this study, by using coarse-grained models and Langevin dynamics, we show that the two effects are additive to each other when they are both present. Both crowding and confinement give rise to the folding temperature and the folding stability of protein. It is shown that the folding free energy change due to crowding in the confined condition can be fitted to Minton scaled particle theory by assuming a linear dependence of the effective radius of the protein unfolded state on the volume fraction of crowders.